AETIOLOGICAL PROFILE OF ACQUIRED ANAEMIA IN A PAEDIATRIC TERTIARY CARE SETTING - Bibi, Saima; Gilani, Syed Yasir Hussain; Shah, Syed Raza Ali; Bibi, Shawana (Journal of Ayub Medical College Abbottabad, 2011)
Background: Anaemia is the commonest haematological disorder frequently faced by clinicians worldwide. The multi-factorial aetiology of the disorder warrants a comprehensive search for the different causes as management plans differ for different disorders. The objective of this study was to identify the different acquired causes of anaemia in our paediatric population. Methods: The study was conducted at the Department of Paediatrics, Ayub Teaching Hospital from April 2009 to April 2010. It was a cross-sectional study. A total of 110 patients were included in the study who presented with anaemia secondary to acquired aetiologies and were assessed clinically using general physical and systemic examination. The salient clinical and laboratory data was retrieved in designed protocol. Results: Out of a total of 110 patients, 61 (55.5%) were male and 49 (44.5%) were female. Mean age of the participants was 48 months. Nutritional anaemia comprising iron deficiency anaemia and megaloblastic anaemia was the leading cause being present in 49 (44.5%) patients followed by Visceral Leishmaniasis in 28 (25.5%) patients. Mean haemoglobin was 4.36 g/dl. Conclusion: Anaemia secondary to acquired causes is a disorder with grave consequences ranging from cognitive and psychomotor dysfunction to mortality in severe cases. Identification of the different acquired causes is important in preventing the disorder by guiding appropriate interventions. Keywords: Anaemia, nutritional, iron deficiency, megaloblastic, Visceral Leishmaniasis